2016
DOI: 10.1111/jonm.12372
|View full text |Cite
|
Sign up to set email alerts
|

Confidence in delegation and leadership of registered nurses in long-term-care hospitals

Abstract: When effective delegation integrates with efficient leadership, staff can deliver optimal care to long-term-care patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 50 publications
0
23
0
6
Order By: Relevance
“…This context is reflected in the way the mistakes are handled, especially in Hospitals A and C. The reports show that they are handled both as a learning source and as a punishment and that is an institutional practice (Haw et al, 2014). In Hospital B, despite institutional encouragement to handle the mistake as a learning source, mistakes are punished by the employees' peers (Vogus & Sutcliffe, 2007 simply because they are uninterested (Maggioni et al, 2015), it is not surprising that nursing technicians prefer separated meetings and have low adherence to hand hygiene or error reporting (Yoon et al, 2016). This suggests a distance between two professional categories that should work in an integrated way, which makes it difficult to improve routines that could mitigate the mistakes made (Vogus & Sutcliffe, 2007).…”
Section: Discussion and Implications For Nursing Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…This context is reflected in the way the mistakes are handled, especially in Hospitals A and C. The reports show that they are handled both as a learning source and as a punishment and that is an institutional practice (Haw et al, 2014). In Hospital B, despite institutional encouragement to handle the mistake as a learning source, mistakes are punished by the employees' peers (Vogus & Sutcliffe, 2007 simply because they are uninterested (Maggioni et al, 2015), it is not surprising that nursing technicians prefer separated meetings and have low adherence to hand hygiene or error reporting (Yoon et al, 2016). This suggests a distance between two professional categories that should work in an integrated way, which makes it difficult to improve routines that could mitigate the mistakes made (Vogus & Sutcliffe, 2007).…”
Section: Discussion and Implications For Nursing Managementmentioning
confidence: 99%
“…The concept of trust in hospital organisations involves delegation that is effective and increases job satisfaction, productivity and cooperation among team members (Yoon, Kim, & Shin, 2016). Trust is closely linked to patient safety, because this is how the professionals are encouraged to notify their own mistakes, allowing an identification of the causes, so reducing adverse events with patients and costs (Haw, Stubbs, & Dickens, 2014).…”
Section: Background and Theoretical Frameworkmentioning
confidence: 99%
“…The concept of trust in healthcare organizations involves a delegation that is effective and able to increase their job satisfaction, productivity, and cooperation among team members (Yoon et al, 2016). Trust is closely linked to patient safety, because it is through it that the professional is encouraged to notify her/his mistakes, allowing the identification of the causes, reducing the adverse events with patients, and avoiding increased costs (Wright, 2013).…”
Section: Trustmentioning
confidence: 99%
“…The leaderships must be committed, and all those involved in the processes of social assistance must participate (Lagrosen, Bäckström, & Wiklund, 2012). Such involvement is reflected in the quality of communication between them (Tibbs & Moss, 2014), as well as the necessary trust to delegate authority to the subordinates (Yoon, Kim, & Shin, 2016), which increases the commitment and productivity, resulting in a better and more efficient assistance (Kaernested & Bragadottir, 2012). As well, we hope to contribute to a deeper understanding of each of the elements necessary for the quality management.…”
Section: Introductionmentioning
confidence: 99%
“…There remains a paucity of information regarding Allied Health Professionals' skills and understanding of the delegation process, nor are opportunities for training delegation skills freely available. Access to training in the area of delegation may be of particular importance as a study in the nursing literature identified a statistically significant increase in delegation confidence for nurses who had participated in training programs (Yoon, Kim, & Shin, 2016). As proposed by Schmidt (2013), delegation and supervisory skills may in the future be part of pre-vocational training for AHPs.…”
Section: 62mentioning
confidence: 99%